Blood pressure and heart rate in aripiprazole once – monthly and paliperidone 1 and 3-month long-acting preparations - GÖREN, MEHMET ZAFER (My University, 2023)
Objective: This study aims to evaluate the blood pressure and heart rates of the patients treated with aripiprazole once-monthly, paliperidone 1-month, and paliperidone 3-month long-acting injections. Patients and Methods: This study was a non-invasive observational study. Subjects using the same long-acting injection preparation for at least four months without skipped injections were assigned to 3 groups according to their treatments. They were screened starting from routine injection day and monthly for four months. Heart rate, systolic blood pressure, and diastolic blood pressure were recorded for each subject. Results: Systolic and diastolic blood pressure among the three treatment groups demonstrated no statistical significance. The heart rate of the paliperidone 3-month group was significantly higher than the aripiprazole once-monthly group. However, the mean heart rate was within the physiological limits. Thus, a clinical significance can hardly be attributed. Conclusion: Aripiprazole once-monthly, paliperidone 1-month, and paliperidone 3-month long-acting injections are non-inferior regarding heart rate, systolic and diastolic blood pressure during the maintenance treatment. Keywords: Long-acting antipsychotic, Hypertension tachycardia, Schizophrenia, Maintenance treatment
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Hypertension tachycardia; Long-acting antipsychotic; Maintenance treatment; Schizophrenia